Exploring the Dynamic Organizational Culture on Ethics and Compliance: Engineering Perspective - Khalid, Khalizani; E. Eldakak, Sam (International Journal of Engineering and Technology, 2018)
To evaluate engineering ethics and the practical compliance practices, the practitioners must understand the dimensions affect ethics and compliance in the engineering community. This study attempts to explore the dimensions of dynamic organization culture, and it affects ethics and compliance in the engineering community. This framework will contribute to the literature of engineering ethics in the context applied ethics since a handful of studies conducted in this domain. Thus, there is a need for a comprehensive model to connect the elements of dynamic organizational culture on engineering ethics and compliance due to the scarcity of literature on engineering ethics and compliance. Since no single method to measure this context in every industry, the transcendental phenomenological approach allows for the cognitive understanding the extent of multiple domains of dynamic organizational culture in engineering ethics and compliance. Dimensions important to engineering ethics and compliance from the perspective of dynamic organizational culture are identified and defined to construct the framework.